Solve for u -3(u+5)+5u=2(u-6)

Math
-3(u+5)+5u=2(u-6)
Simplify -3(u+5)+5u.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-3u-3⋅5+5u=2(u-6)
Multiply -3 by 5.
-3u-15+5u=2(u-6)
-3u-15+5u=2(u-6)
Add -3u and 5u.
2u-15=2(u-6)
2u-15=2(u-6)
Simplify 2(u-6).
Tap for more steps…
Apply the distributive property.
2u-15=2u+2⋅-6
Multiply 2 by -6.
2u-15=2u-12
2u-15=2u-12
Move all terms containing u to the left side of the equation.
Tap for more steps…
Subtract 2u from both sides of the equation.
2u-15-2u=-12
Combine the opposite terms in 2u-15-2u.
Tap for more steps…
Subtract 2u from 2u.
0-15=-12
Subtract 15 from 0.
-15=-12
-15=-12
-15=-12
Since -15≠-12, there are no solutions.
No solution
Solve for u -3(u+5)+5u=2(u-6)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top